Quality of life of the nursing caregiver and its relationship with care - Everton Fernando Alves (Universidade de Fortaleza, 2013)
Objective: To identify aspects that affect the quality of life of nursing caregivers and their relationship with care in an Intensive Care Unit for Adults (A-ICU). Methods: This was a descriptive study with qualitative approach, taking as subjects 21 professionals who constitute the nursing staff of the A-ICU of a school hospital in Maringá-PR. Unstructured interview was used as a strategy to collect data, conducted between May and June 2009. Data analysis was based on the method of content analysis. The categories identified were: overlooking improvement in quality of life related to the resources in an A-ICU; the quality of life influencing the form of care; interpersonal relationships into the health team reflecting on the quality of life and care. Results: The analysis of caregivers' speech and the results of the observation showed that there is correlation between the aspects they consider influential in their quality of life and the way of caring for patients in an A-ICU. Conclusion: The findings indicate that, among the influential aspects, the stressful factors overlap the enhancing ones. From this perspective, dealing with caregiver's suffering might be the starting point for the improvement in quality of care in an A-ICU